Omics-Based Comparison of Fungal Virulence Genes, Biosynthetic Gene Clusters, and Small Molecules in Penicillium expansum and Penicillium chrysogenum - Holly P. Bartholomew; Christopher Gottschalk; Bret Cooper; Michael R. Bukowski; Ronghui Yang; Verneta L. Gaskins; Dianiris Luciano-Rosario; Jorge M. Fonseca; Wayne M. Jurick (Journal of Fungi)
Penicillium expansum is a ubiquitous pathogenic fungus that causes blue mold decay of apple fruit postharvest, and another member of the genus, Penicillium chrysogenum, is a well-studied saprophyte valued for antibiotic and small molecule production. While these two fungi have been investigated individually, a recent discovery revealed that P. chrysogenum can block P. expansum-mediated decay of apple fruit. To shed light on this observation, we conducted a comparative genomic, transcriptomic, and metabolomic study of two P. chrysogenum (404 and 413) and two P. expansum (Pe21 and R19) isolates. Global transcriptional and metabolomic outputs were disparate between the species, nearly identical for P. chrysogenum isolates, and different between P. expansum isolates. Further, the two P. chrysogenum genomes revealed secondary metabolite gene clusters that varied widely from P. expansum. This included the absence of an intact patulin gene cluster in P. chrysogenum, which corroborates the metabolomic data regarding its inability to produce patulin. Additionally, a core subset of P. expansum virulence gene homologues were identified in P. chrysogenum and were similarly transcriptionally regulated in vitro. Molecules with varying biological activities, and phytohormone-like compounds were detected for the first time in P. expansum while antibiotics like penicillin G and other biologically active molecules were discovered in P. chrysogenum culture supernatants. Our findings provide a solid omics-based foundation of small molecule production in these two fungal species with implications in postharvest context and expand the current knowledge of the Penicillium-derived chemical repertoire for broader fundamental and practical applications.